Utilization of Google Drive Application for Archival Document Storage - Syahfitri, Cindy Agathia Dwi; Hamidah; Khairina Afni (Global Action and Education for Society, 2026)
This study aims to analyze the utilization of the Google Drive application as a medium for document archiving at SMK Swasta Taruna Bangsa Sawit Seberang in the 2024–2025 academic year. The research was motivated by the persistence of manual archiving systems in schools, which often cause difficulties in document retrieval, data loss risks, and low administrative efficiency. This study employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the principal and administrative staff. The findings reveal that the use of Google Drive facilitates document storage, management, and retrieval, enhances time efficiency, and strengthens data security through encryption systems and access control features. However, several challenges were identified, including limited digital literacy among users, dependence on internet connectivity, and the restricted capacity of free storage. Overall, the study concludes that Google Drive serves as an effective solution for supporting school archive digitalization, provided that its implementation is accompanied by proper technical training and well-defined management policies.